How do delirium motor subtypes differ in phenomenology and contributory aetiology? a cross-sectional, multisite study of liaison psychiatry and palliative care patients. Issue 4 (14th April 2021) - Glynn, Kevin; McKenna, Frank; Lally, Kevin; O'Donnell, Muireann; Grover, Sandeep; Chakrabarti, Subho; Avasthi, Ajit; Mattoo, Surendra K; Sharma, Akhilesh; Ghosh, Abhishek; Shah, Ruchita; Hickey, David; et al.
Abstract : Objectives: To investigate whether delirium motor subtypes differ in terms of phenomenology and contributory aetiology. Design: Cross-sectional study. Setting: International study incorporating data from Ireland and India across palliative care, old age liaison psychiatry and general adult liaison psychiatry settings. Participants: 1757 patients diagnosed with delirium using criteria from the Diagnostic and Statistical Manual of Mental Disorders, Fourth edition (DSM IV). Primary and secondary outcome measures: Hyperactive, mixed and hypoactive delirium subtypes were identified using the abbreviated version of the Delirium Motor Subtype Scale. Phenomenology was assessed using the Delirium Rating Scale Revised. Contributory aetiologies were assessed using the Delirium Aetiology Checklist (DEC), with a score >2 indicating that the aetiology was likely or definitely contributory. Results: Hypoactive delirium was associated with dementia, cerebrovascular and systemic infection aetiologies (p<0.001) and had a lower overall burden of delirium symptoms than the other motor subtypes. Hyperactive delirium was associated with younger age, drug withdrawal and the DEC category other systemic aetiologies (p<0.001). Mixed delirium showed the greatest symptom burden and was more often associated with drug intoxication and metabolic disturbance (p<0.001). All three delirium motor subtypes had similar levels of impairment in attention and visuospatial functioning but differed significantly when compared with no subtype (p<0.001). Conclusions: This study indicates a pattern of aetiology and symptomatology of delirium motor subtypes across a large international sample that had previously been lacking. It serves to improve our understanding of this complex condition and has implications in terms of early detection and management of delirium.